Hispanic Latin America, Spain and the Spanish-speaking Caribbean: A rich source of reference material for public health, epidemiology and tropical medicine - Williams, John R (BioMed Central, 2008)
There is a multiplicity of journals originating in Spain and the Spanish-speaking countries of Latin America and the Caribbean (SSLAC) in the health sciences of relevance to the fields of epidemiology and public health. While the subject matter of epidemiology in Spain shares many features with its neighbours in Western Europe, many aspects of epidemiology in Latin America are particular to that region. There are also distinctive theoretical and philosophical approaches to the study of epidemiology and public health arising from traditions such as the Latin American social medicine movement, of which there may be limited awareness. A number of online bibliographic databases are available which focus primarily on health sciences literature arising in Spain and Latin America, the most prominent being Literatura Latinoamericana en Ciencias de la Salud (LILACS) and LATINDEX. Some such as LILACS also extensively index grey literature. As well as in Spanish, interfaces are provided in English and Portuguese. Abstracts of articles may also be provided in English with an increasing number of journals beginning to publish entire articles written in English. Free full text articles are becoming accessible, one of the most comprehensive sources being the Scientific Electronic Library Online (SciELO). There is thus an extensive range of literature originating in Spain and SSLAC freely identifiable and often accessible online, and with the potential to provide useful inputs to the study of epidemiology and public health provided that any reluctance to explore these resources can be overcome. In this article we provide an introduction to such resources.